2018
DOI: 10.21307/ane-2018-030
|View full text |Cite
|
Sign up to set email alerts
|

Acute cold allodynia induced by oxaliplatin is attenuated by amitriptyline

Abstract: Oxaliplatin is a third-generation, platinum-based antitumor drug used to treat colorectal cancer. Since its main adverse effect is neuropathic pain resulting from chemotherapy-induced peripheral neuropathy (CIPN), this drug is used to study the neurobiology of CIPN in rodents and to search for analgesics that could attenuate neuropathic pain symptoms-cold and tactile allodynia that develop in most of the oxaliplatin-treated subjects. In this research, testing across various temperatures, we assessed the cold r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…For all temperatures tested, early‐phase cold allodynia was fully developed 3 hr after oxaliplatin injection, so for further experiments that involved measurements of predrug latencies to pain reaction this time point was chosen. Earlier studies also confirmed that after a single dose of oxaliplatin, cold allodynia is stable for at least 7 days, and therefore, this period was involved in the in vivo testing (Furgała, Sałat, et al., ; Nakagawa & Kaneko, ). It is worth noting that although the device we use (hot/cold plate apparatus, Bioseb, France) is supplied with a thermo‐controller which enables to maintain the temperature constantly at the desired level, each day prior to the testing session, the temperature of the plate was carefully checked by using a thermocouple probe. We used one (type BM807) purchased from Brymen Technology Corporation (Taiwan), but any device of this type and precision can be used.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…For all temperatures tested, early‐phase cold allodynia was fully developed 3 hr after oxaliplatin injection, so for further experiments that involved measurements of predrug latencies to pain reaction this time point was chosen. Earlier studies also confirmed that after a single dose of oxaliplatin, cold allodynia is stable for at least 7 days, and therefore, this period was involved in the in vivo testing (Furgała, Sałat, et al., ; Nakagawa & Kaneko, ). It is worth noting that although the device we use (hot/cold plate apparatus, Bioseb, France) is supplied with a thermo‐controller which enables to maintain the temperature constantly at the desired level, each day prior to the testing session, the temperature of the plate was carefully checked by using a thermocouple probe. We used one (type BM807) purchased from Brymen Technology Corporation (Taiwan), but any device of this type and precision can be used.…”
Section: Methodsmentioning
confidence: 75%
“…For further pain tests, only mice with baseline latencies ≥40 s were chosen. In this assay, the maximum observation time (i.e., cut‐off time) was 60 s. In our earlier experiments, we tested a broader temperature range—from 1 to 4°C (Furgała, Sałat, & Sałat, ) and cold allodynia was measured at various time points: 2, 3, 4, 6, 24 hr, 3, and 7 days after oxaliplatin. We found that the development of cold allodynia could be observed as early as 2 hr after oxaliplatin administration, which is consistent with the previously published data (Nakagawa & Kaneko, ).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of 1 on cold pain threshold was assessed using the cold plate test [ 73 , 74 ]. In this assay, after the establishment of predrug latency to pain reaction for each animal, the mice were treated with the test compounds and 60 min later they were placed on the cold plate apparatus (Hot/cold plate, Bioseb, France) set at 2.5 °C and were observed for the appearance of a nocifensive response (hind paw licking, shaking, jumping or abnormal movements).…”
Section: Methodsmentioning
confidence: 99%
“…Here, the animal placed on the cooled plate at 5°C and the time to induce nociceptive behaviour indicated by shivering and paw licking recorded as the response time (Furgula et.al., 2018).…”
Section: Methodsmentioning
confidence: 99%